5 | ( | 2 | x | − | 1 | ) | = | 10 | − | 2 | ( | x | − | 3 | ) |
Left side of the equation = | 5 | × | 2 | x | − | 5 | × | 1 |
= | 10 | x | − | 5 |
10 | x | − | 5 | = | 10 | − | 2 | ( | x | − | 3 | ) |
Right side of the equation = | 10 | − | 2 | x | + | 2 | × | 3 |
= | 10 | − | 2 | x | + | 6 |
= | 16 | − | 2 | x |
10 | x | − | 5 | = | 16 | − | 2 | x |
10 | x | + | 2 | x | = | 16 | + | 5 |
12 | x | = | 16 | + | 5 |
12 | x | = | 21 |
x | = | 21 | ÷ | 12 |
= | 21 | × | 1 12 |
= | 7 | × | 1 4 |
x | = | 7 4 |
x | = | 1.75 |